Handbook of research on driving industrial competitiveness with innovative design principles - Farinha, Luis M. Carmo, 1975-; Raposo, Daniel (Advances in business strategy and competitive advantage., 2020)
"This book focuses on the relationship between innovation and competitiveness in business"--